Electron distribution functions in the diffusion region of asymmetric magnetic reconnection. Issue 5 (7th March 2016) - Bessho, N.; Chen, L.‐J.; Hesse, M.
Abstract: We study electron distribution functions in a diffusion region of antiparallel asymmetric reconnection by means of particle‐in‐cell simulations and analytical theory. At the electron stagnation point, the electron distribution comprises a crescent‐shaped population and a core component. The crescent‐shaped distribution is due to electrons coming from the magnetosheath toward the stagnation point and accelerated mainly by electric field normal to the current sheet. Only a part of magnetosheath electrons can reach the stagnation point and form the crescent‐shaped distribution that has a boundary of a parabolic curve. The penetration length of magnetosheath electrons into the magnetosphere is derived. We expect that satellite observations can detect crescent‐shaped electron distributions during magnetopause reconnection. Key Points: Meandering electrons accelerated by the normal electric field determine a crescent distribution Crescent‐shaped populations exist near the electron stagnation point and in the outflow region The distance of penetration into the magnetosphere by magnetosheath electrons is derived